Immunogenic assessment of plant-produced Human papillomavirus type 16 chimaeric L1:L2 virus-like particles and the production of an encapsidated therapeutic DNA vaccine candidate - Chabeda, Eva Aleyo (Department of Molecular and Cell Biology, 2018)
Cervical cancer caused by infection with Human papillomavirus (HPV) is the 4th most common cancer in women globally, and results in an estimated 266 000 deaths every year. Current vaccines are based on the immunodominant L1 major capsid protein, which assembles into virus-like particles (VLPs) that are highly effective in type-specific prevention of cervical infection. However, these vaccines are produced in expensive cell culture systems, are type-specific and do not induce the regression of established infections. The cervical cancer burden (~80%) is mainly in developing countries due to limited healthcare resources, therefore there is a need for more broadly protective and affordable vaccines. Plants provide an alternative platform to produce cheaper vaccines, given their scalability, rapid production and low risk of contamination. The L2 minor capsid protein has sequence regions that are highly conserved across several HPV types, and HPV-16 L2 peptides 108-120, 65-81, 56-81 and 17-36 have been shown to elicit cross-neutralising antibodies. To increase the immunogenicity of L2, second-generation L1:L2 chimaeric VLP (cVLP) vaccines have been investigated. In this study, the 4 L2 peptides above were used to generate plant-produced HPV-16-derived L1:L2 chimaeras. The L2 epitopes were substituted into the DE loop of HPV-16 L1 at position 131 (SAC) or between the helix 4 and β-J structural region at position 431 (SAE). All chimaeras were transiently expressed in Nicotiana benthamiana via Agrobacterium-mediated transfer. Optimisation of expression was conducted by comparing protein expression levels over several days using 4 plant expression vectors, with the highest yields obtained by targeting protein to the chloroplast or with the use of a self-replicating vector. The chloroplast targeted SAC chimaeras predominantly assembled into higher order structures (T=1 VLPs and T=7 VLPs), whereas SAE chimaeras assembled into capsomeres or formed aggregates, indicating that the length, sequence and substitution position of L2 epitopes affects VLP assembly. All SAC chimaeras in addition to SAE 65-81 (smaller epitope not previously tested in chimaeras) were used in vaccination studies in mice, and their immunogenic potential analysed in pseudovirion-based neutralisation assays (PBNAs). Of the 7 heterologous HPVs tested, cross-neutralisation was observed with HPV-11, -18 and -58. Only the anti-SAE 65-81 serum showed neutralisation of homologous HPV-16, suggesting that antibodies detected from all candidate vaccines were mostly non-neutralising, and that the position of the L2 epitope display is critical to maintaining L1-specific neutralising epitopes. Lastly, to address the lack of therapeutic efficacy of current vaccines, I aimed to develop a novel E7 DNA vaccine delivered by plant-made pseudovirions (PsVs). A geminivirus-derived self-replicating plasmid encoding a shuffled E7 (E7SH) sequence that has no transformation ability but contains natural cytotoxic T-lymphocyte epitopes, was constructed using Goldenbraid technology and co-expressed in plants with HPV-16 or HPV-35 L1- and L2-encoding expression vectors. The pseudogenome was successfully encapsidated into plant-made PsVs. These PsVs were capable of infecting mammalian cells and encapsidated replicons expressed E7SH showing the promise of this candidate vaccine as a future combination prophylactic and therapeutic vaccine.